KETERAMPILAN BERPIKIR KRITIS MAHASISWA/MAHASISWI YANG MENYERTAI EKSPEDISI PENDAKIAN GUNUNG DI MALAYSIA - Mustafa, Munauwar; Ismail, Mohd Azril; Poespowidjojo, Donny Abdul Latief Abdul Latief (TINGKAP, 2016)
This study was carried out to look at the effect of participation in well known adventure mountaineering expeditions in Peninsular Malaysia, namely Chamah-Ulu Sepat and Trans Titiwangsa expeditions on the score of participantsâ€™ critical thinking skill. The study population were public university students who participated in one of the aforementioned expeditions within the period of data collection which was during the long break during the second semester academic session and the first semester of academic session. This study utilizes an established instrument developed by Watson and Glaser which is potentially able to help achieve the study objective, taking into consideration the validity and reliability of the construct and its suitability with the respondents. The findings of the study reveal that there is a significant difference between the score of critical thinking skill of the participants before and after the adventure climb.Â  However, mean scores between the two expeditions reveals that they do not differ significantly.Therefore, it can be concluded that students participation in mountaineering expeditions can be used as a training method to enhance their critical thinking skills. The study adds to another approach of increasing the level of critical thinking skill through adventure mountaineering expeditions in Peninsular Malaysia.Keywords: Critical Thinking Skills, Training and Development, Incidental Learning, Adventure Training